APLIKASI SMS GATEWAY UNTUK PELAYANAN KEUANGAN MTS AL ASROR GUNUNG PATI SEMARANG (Information Technology and Telematics, 2015)
Abstract : SMS(Short Message Service) is areliablemode ofcommunicationtoday, SMSis aservice providedby themobileoperator tosendandreceiveshort messages. SMSconsidered to be verypractical, inexpensive, andefficient. The behavior ofmobile userstodaycanbe saidthateveryincoming SMSorevenlikelywill be readbecausethe nature ofthepersonalmobile phone. In additiontosendingmessages betweenmobile users, SMSis alsosuitabletobe appliedandinteractwithacomputer-based informationsystems. This researchaimstomakeSMS Gateway applicationthatcanassistthe administrationin submittingpaymentinformationto parentsMTSAlAsrorMountPatiSemarang. SMS Gateway applicationforfinancialservicesMTSAlAsrorMountPatiSemarangusinga specialmodemforSMSwithWavecomM1306brands. toperformdatabase managementcan be openedviathe GoogleChromebrowser. Keywords: FinancialServices, MTSAlAsror, SMSGateway, Gammu